Domino donor heart: possibility of using cardiac valves - Marcelino, César Augusto Guimarães; Fusco, Carine Cristiane; Araújo , Mara Nogueira; Ayoub, Andréa Cotait (Brazilian Journal of Transplantation, 2010)
Introduction: Among several heart diseases, the malfunctioning of the human heart valves is outstanding, requiring replacement with biological or metal valves or their replacement by transplantation of human valves coming from deceased donors or living donors as native heart from heart transplant domino donor recipient. Purpose: To investigate the possibility of using the valve tissue from hearts removed in transplantation during the period between 1991 and 2007. Method: This exploratory, descriptive and documentary study was performed in a Public Hospital in Sao Paulo/Brazil, which is reference in cardiovascular disease assistance. Results: The sample consisted of 202 transplanted hearts, prevailing male with 155 (76.7%) cases, and 47 with age between 56-70 years old (31.1%). As to the base diagnosis, only 51 (25.2%) had such information, and from these, the most frequent was dilated cardiomyopathy in 16 cases (31.4%). From 202 hearts assessed, 114 (56.4%) presented anatomopathological report; from these, 69 (59.6%) reported that valves had no alteration, while 46 (40.4%) informed the presence of altered valves. Heart valves with less frequency of alterations were: pulmonary in 82 cases (71.9%) and aortic valves in 81 cases (71.1%). Conclusion: The anatomopathological study of hearts collected from heart receptors showed the existence of heart valves which could be used in valve transplants, mainly aortic valve.